Safety and efficacy of evobrutinib in relapsing multiple sclerosis (evolutionRMS1 and evolutionRMS2): two multicentre, randomised, double-blind, active-controlled, phase 3 trials - Montalban, Xavier; Vermersch, Patrick; Arnold, Douglas L; Bar-Or, Amit; Cree, Bruce A C; Cross, Anne H; Kubala Havrdova, Eva; Kappos, Ludwig; Stuve, Olaf; Wiendl, Heinz; Wolinsky, Jerry S; Dahlke, Frank; et al. (The Lancet. Neurology, 2024)
BACKGROUND: Evobrutinib, a Bruton's tyrosine kinase (BTK) inhibitor, has shown preliminary efficacy in people with relapsing multiple sclerosis in a phase 2 trial. Here, we aimed to compare the safety and efficacy of evobrutinib with the active comparator teriflunomide in people with relapsing multiple sclerosis. METHODS: EvolutionRMS1 and evolutionRMS2 were two multicentre, randomised, double-blind, double-dummy, active-controlled, phase 3 trials conducted at 701 multiple sclerosis centres and neurology clinics in 52 countries. Adults aged 18-55 years with relapsing multiple sclerosis (Expanded Disability Status Scale [EDSS] score of 0·0-5·5) were included. Participants were randomly assigned (1:1) using a central interactive web response system to receive either evobrutinib (45 mg twice per day with placebo once per day) or teriflunomide (14 mg once per day with placebo twice per day), all taken orally and in an unfasted state, with randomisation stratified by geographical region and baseline EDSS. All study staff and participants were masked to the study interventions. The primary endpoint for each study was annualised relapse rate based on adjudicated qualified relapses up to 156 weeks, assessed in the full analysis set (defined as all randomly assigned participants) with a negative binomial model. These studies are registered with ClinicalTrials.gov (NCT04338022 for evolutionRMS1 and NCT04338061 for evolutionRMS2, both are terminated). FINDINGS: The primary analysis was done using data for 2290 randomly assigned participants collected from June 12, 2020, to Oct 2, 2023. 1124 participants were included in the full analysis set in evolutionRMS1 (560 in the evobrutinib group and 564 in the teriflunomide group) and 1166 in evolutionRMS2 (583 in each group). 751 (66·8%) participants were female and 373 (33·1%) were male in evolutionRMS1, whereas 783 (67·2%) were female and 383 (32·8%) were male in evolutionRMS2. Annualised relapse rate was 0·15 (95% CI 0·12-0·18 with evobrutinib vs 0·14 [0·11-0·18] with teriflunomide (adjusted RR 1·02 [0·75-1·39]; p=0·55) in evolutionRMS1 and 0·11 (0·09-0·13 vs 0·11 [0·09-0·13]; adjusted RR 1·00 [0·74-1·35]; p=0·51) in evolutionRMS2. The pooled proportion of participants with any treatment-emergent adverse event (TEAE) was similar between treatment groups (976 [85·6%] of 1140 with evobrutinib vs 999 [87·2%] of 1146 with teriflunomide). The most frequently reported TEAEs were COVID-19 (223 [19·6%] with evobrutinib vs 223 [19·5%] with teriflunomide), alanine aminotransferase increased (173 [15·2%] vs 204 [17·8%]), aspartate aminotransferase increased (110 [9·6%] vs 131 [11·4%]), and headache (175 [15·4%] vs 176 [15·4%]). Serious TEAE incidence rates were higher with evobrutinib than teriflunomide (86 [7·5%] vs 64 [5·6%]). Liver enzyme elevations at least 5 × upper limit of normal were more common with evobrutinib than with teriflunomide, particularly in the first 12 weeks (55 [5·0%] vs nine [<1%]). Three people who received evobrutinib and one who received teriflunomide met the biochemical definition of Hy's law; all cases resolved after discontinuation of treatment. There were two deaths (one in each group), neither related to study treatment. INTERPRETATION: The efficacy of evobrutinib was not superior to that of teriflunomide. Together, efficacy and liver-related safety findings do not support the use of evobrutinib in people with relapsing multiple sclerosis. FUNDING: Merck.
Keywords: dospělí; Agammaglobulinaemia Tyrosine Kinase; Female; toluidiny; pyrimidiny; inhibitory proteinkinas; Adult; výsledek terapie; mladý dospělý; ženské pohlaví; piperidiny; hydroxybutyráty; Adolescent; relabující-remitující roztroušená skleróza; lidé; dvojitá slepá metoda; proteinkinasa BTK; krotonáty; Toluidines; Treatment Outcome; Middle Aged; Double-Blind Method; Male; Protein Kinase Inhibitors; Crotonates; Multiple Sclerosis, Relapsing-Remitting; nitrily; Piperidines; Young Adult; Nitriles; lidé středního věku; mužské pohlaví; Hydroxybutyrates; mladiství; Pyrimidines; Humans